SEDIMENT AND COASTLINE CHANGE ANALYSIS OF SUNGAI KAYU ARA VILLAGE, SIAK DISTRIC, RIAU - Suci Monika Putri; Rifardi Rifardi; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe main purpose of study was to find out characteristics of sediment and velocity of coastline change in Sungai Kayu Ara Village which is located off the Siak district, Riau. Sediment samples were collected at 3 stations in coastal area of Meskom Village in September 2019. Stations 1 and 2 are located in the residential area and Station 3 is in the vicinity of the Ara Permai Mangrove Tourism Forest. Coastline change analysis used image data by Landsat 5 TM (1997 and 2009) and Landsat 8 LDCM (2019) which processed by ArcMap10.3..Sungai Kayu Ara village is characterized by sediment fine silt and very coarsed skewed indicated that abrasion and sedimentasion influenced of current and wave. Moderately sorting indicated that the sediment coastal of Sungai Kayu Ara village has rather stable environmentally. Interpretation of image data indicated that the coastal area has been abraded at station 1, that is 84,268 meter/year seen from 1997 to 2019.Keywords: Sediment, Coastline change, Abrasion, Remote Sensing.